KOMUNIKASI ORGANISASI KEPALA DESA DALAM MEMBANGUN KESADARAN MASYARAKAT DESA TERHADAP PEMBANGUNAN DESA - Puput Purnama Sari; Lutfi Basit (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2018)
ABSTRACTCommunication used by everyone, wherever and anytime. In addition, communication can be conducted in an organization, both in organization to an enterprise, the government and forth. In an organization people will communicate. As leaders of communication, communication leaders on the community and other. Communication important to a organization because communication is instrumental for members of an organization to can work together in doing activity of management, which is to reach organizational goals that went forth before. Research is called communication organization in raise awareness of the community towards village development aimed at to see how communication organization in raise awareness of the community towards village development to villagers / nagori kampung Lalang of subdistrict Ujung Padang  of the District Simalungun. The kind of research used in this research is research deskriftif with a qualitative approach was adopted. The source of information as many as 10 ( ten ) the. The source of information having a profusion of being divergent as the head of the village, village officials, teachers, tens of thousands of workers, from self employed, and farmers. Engineering data collection was to interview and analyzing through three rounds, the reduction of data, data, and withdrawal conclusions and verification. The result of this research organization is communication the village in building public awareness of rural development is good. The community has been having awareness of the building village. They have participated in rural development by the village. Keyword: Communication, Communication organization, The Village Chief